Accounting for dummies - Tracy, John A.; Tracy, Tage C. (Tantor Media, Inc., 2022)
Few skills are as useful as a basic understanding of accounting language. And with the right resources, learning the language of business can be intuitive, empowering, and fun. Accounting For Dummies is the perfect place to start, whether you're operating a small business, just need help managing the family budget, or you're a rising star in corporate America. It's a financial blueprint for the everyday person, easy-to-understand, and full of practical advice. You'll learn the basic ABC's of accounting, how to read and understand financial statements, create best in class budgets & forecasts, craft profitable business plans, take control of your own finances, gain insight on how companies get money from investors and banks, and avoid common money mistakes that trip up even the best of us. As a useful tool for business or as a guide to your personal finances, nothing compares to accounting mastery. And once you've nailed the basics, you'll wonder how you ever lived without this universal and beautiful language.
Online resource; title from title details screen (O'Reilly, viewed May 4, 2022)
Keywords: Accounting; Accounting -- Self-instruction; Bookkeeping; Tenue des livres; Downloadable audio books; Audiobooks; Self-instruction; Livres audio